KNOWLEDGE COMMUNICATION IN GLOBAL ORGANISATIONS making sense of virtual teams. - Petersen, Nils Braad ([S.l.] : ROUTLEDGE, 2022)
While organisations become more and more global, they also become more and more dispersed and virtual. This challenges the sense of a shared organisational identity and the ability of employees to communicate personally held knowledge. To address these challenges this book offers an innovative multidisciplinary approach to knowledge communication in global organisations. The book develops a multidisciplinary analytical lens through which to understand employee identity formations and knowledge communication practises. Using detailed analyses of interviews from a real organisation, the book builds an understanding of how 21st century employees make sense of a virtual organisational reality characterised by multiple simultaneous projects and virtual, dispersed teams. These analyses are conducted using a new discourse analysis method for analysing research interviews, Discursive Sensemaking Analysis. Using these methods and findings, researchers, project managers and HR professionals will be able to analyse their own organisations to discover how employees make sense of the complexity of 21st century global organisations.
OCLC-licensed vendor bibliographic record.
Keywords: Virtual work teams -- Management; Telecommunication -- Social aspects; Knowledge, Sociology of; International business enterprises; Communication in organizations; Organizational change; BUSINESS & ECONOMICS / Organizational Behavior; BUSINESS & ECONOMICS / Management